Development of Android-based Interactive Multimedia in Python Basic Programming Material for Grade 10 Senior High School - Gayatri, Tiara Nisya; Maryono, Dwi; Yuana, Rosihan Ari (Universitas Sebelas Maret, 2024)
This research is motivated by the use of learning media that still does not meet the needs of students and raises several learning problems in the informatics learning process, especially basic programming material. students feel bored and have difficulty understanding the material presented by the teacher so more learning hours are needed. This study aims to develop Android-based interactive learning media on Python basic programming material for grade 10 high school. This study uses the Research and Development (R&D) method with the ADDIE development model. The ADDIE development model consists of 5 stages, namely: (1) Analysis, (2) Design, (3) Development (4) Implementation, and (5) Evaluation. Data collection techniques used were interviews, questionnaires, and literature studies. The analysis technique used is a quantitative descriptive analysis technique. The interactive features developed are interesting Python basic programming materials with learning videos, live code, and quizzes. The results of application validation assessment by media experts were declared very feasible with a percentage score of 94.05% and the results of validation assessment by material experts were declared feasible with a percentage score of 75%. Student response assessment results obtained a percentage score of 81.66% accepted by students. Based on these results, it can be concluded that Android-based interactive learning media on basic Python programming material is suitable for use as a learning medium for informatics subjects and can be an alternative solution to address student learning problems.